Social Representations of the Past: The Coup of September 11, 1973 according to chil- dren and adolescents from la Ligua commune in Valparaiso, Chile - Faúndez Abarca, Ximena (2020)
This paper analyzes the social representations of September 11, 1973, the date of the coup in Chile, of a sample of 1053 boys, girls and adolescents from Valparaíso. Participants ranged in age between 11 and 18 (M=14.83; SD=1.89). The Participatory Diagnostic Questionnaire in Childhood and Adolescence was used. The data were analyzed in two phases; first dictionaries were constructed, and then analyses of hierarchical clusters, multidimensional scaling and multiple correspondences were performed. Almost half of the participants failed to associate concepts with the date or associated concepts to other historical events. For those who did relate the concepts, they discuss negative consequences at a social and personal level, such as human rights violations, death, suffering and political violence. This is combined with the belief of a foundational violence that would have made social progress possible.